TRINITIES IN DISCOVERING MEANINGS ON LITERATURE INSTRUCTIONAL SCHEME ON LITERARY STUDIES - Sarif Syamsu Rizal (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2016)
This paperâ€™s title is Trinities in Discovering Meaning on Literature aiming to discuss Instructional Scheme on Literary Studies. Methods of the study consist of qualitative design in explaining discourse, library research in collecting data, and problem-based approach in answering the problem statements, the three-substances of which are significant to English teaching on literary studies. Literary studies are the humanistic studies of literature and literary research is the final project for the students who are going to complete their study at notably English Literature Study Programs. Their final project must compose scientific written report. It is in the form of writing literary analysis. The most significant point to emphasize is that literary analysis is an argument about a literary work and that whatever recommendations are made throughout the interpretation from the need to write persuasively about a clear, scientific, and debatable thesis. The writing on literary analysis is getting branched out being up to date in any academic atmosphere, of course, in line with the development of theory, history, and criticism on literature. This article is an alternative way for instructional manuscript blending theoretical or conceptual ideas with practical ideas about an alternative pedagogy in the area of English literary studies teaching and research. It is designed to help teachers specialized in literature introducing the writing literary analysis to their students. I deliver this article because I am sure that the trinities in the science of literature must be comprehended by the teachers before they transmit it in the classroom activities in teaching English Literary Studies. The term â€œTrinitiesâ€ above is going to be explained in a discussion.Keywords: trinities, literature, instructional scheme, literary studies